(untitled) - Damrosch, David (New York, 2010)
This volume presents extensive selections from a wide range of underrepresented female writers like Mary Wollstonecraft, Dorothy Wordsworth, and Mary Robinson. “Perspectives” sections shed light on the period as a whole
Keywords: English literature,Great Britain,Văn học Anh,Anh Quốc; Civilization,Nền văn minh; 20th century,20th century,Thế kỷ 20,Thế kỷ 20